Recent Publications (Quarterly Journal of Economics, 1934)
Recent Publications Get access The Quarterly Journal of Economics, Volume 49, Issue 1, November 1934, Pages 167–171, https://doi.org/10.1093/qje/49.1.167 Published: 01 November 1934